2017
DOI: 10.1104/pp.16.01494
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor MYB29 Is a Regulator of ALTERNATIVE OXIDASE1a

Abstract: Plants sense and integrate a variety of signals from the environment through different interacting signal transduction pathways that involve hormones and signaling molecules. Using () gene expression as a model system of retrograde or stress signaling between mitochondria and the nucleus, MYB DOMAIN PROTEIN29 (MYB29) was identified as a negative regulator ( [] mutant) in a genetic screen of Arabidopsis (). mutants have increased levels of AOX1a transcript and protein compared to wild type after induction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 139 publications
1
25
0
Order By: Relevance
“…A positive regulator of glucosinolate metabolism in Arabidopsis, MYB29, has been previously shown to be a negative regulator of AOX expression (Zhang et al, 2017), and this may account for the reduction of AOX observed in the dgs1-1 lines ( Figure 5A). This supports the suggestion that there is an antagonistic relationship in the induction of glucosinolate metabolism and AOX (Zhang et al, 2017), with the former favored in the dgs1-1 lines. Glucosinolate biosynthesis is also regulated by jasmonic acid, and there is an antagonistic interaction between the jasmonic and salicylic acid hormone signaling pathways in Arabidopsis (Thaler et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A positive regulator of glucosinolate metabolism in Arabidopsis, MYB29, has been previously shown to be a negative regulator of AOX expression (Zhang et al, 2017), and this may account for the reduction of AOX observed in the dgs1-1 lines ( Figure 5A). This supports the suggestion that there is an antagonistic relationship in the induction of glucosinolate metabolism and AOX (Zhang et al, 2017), with the former favored in the dgs1-1 lines. Glucosinolate biosynthesis is also regulated by jasmonic acid, and there is an antagonistic interaction between the jasmonic and salicylic acid hormone signaling pathways in Arabidopsis (Thaler et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Upregulation of glucosinolate biosynthesis and metabolism has been linked to responses to drought stress (Eom et al, 2018). A positive regulator of glucosinolate metabolism in Arabidopsis, MYB29, has been previously shown to be a negative regulator of AOX expression (Zhang et al, 2017), and this may account for the reduction of AOX observed in the dgs1-1 lines ( Figure 5A). This supports the suggestion that there is an antagonistic relationship in the induction of glucosinolate metabolism and AOX (Zhang et al, 2017), with the former favored in the dgs1-1 lines.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Zhang et al (2017a) identified MYB DO-MAIN PROTEIN29/RAO7 as an additional transcription factor that has a negative, albeit indirect, regulatory impact on downstream genes related to mitochondrial stress, including AOX1a, but notably also WRKY40 and ANAC053. Since WRKY40 in turn regulates expression of ABI4 (Liu et al, 2012b) it appears that the transcription factors in retrograde signaling form expression networks.…”
Section: Proteins Regulating Nuclear Transcription In Mitochondrial Smentioning
confidence: 99%
“…In Arabidopsis thaliana , great progress has been made to identify a set of nuclear genes whose expression is responsive to mitochondrial dysfunction (Schwarzländer et al ). Proteins controlling the transcriptional response of such genes have been identified (Giraud et al , Geisler et al , Vanderauwera et al , De Clercq et al , Van Aken et al , Ng et al , , Zhang et al ), and it has been shown that the transcriptional changes result in acclimation responses that benefit the plant (Van Aken et al ). Hence, these stress response pathways have become an important model for the study of retrograde (mitochondrion‐to‐nucleus) signaling (Ng et al , Wagner et al , Wang et al ).…”
Section: Introductionmentioning
confidence: 99%